Agency costs and investment behavior - Viktor Dorofeenko; Gabriel S. Lee; Kevin D. Salyer (Institute for Advanced Studies (IHS), 2005)
How do differences in the creit channel affect investment behavior in the U.S. and the Euro area? To analyze this question, we calibrate an agency cost model of business cycles. We focus on two key components of the lending channel, the default premium associated with bank loans and bankruptcy rates, to identify the differences in the U.S. and European financial sectors. Our results indicate that the differences in financial structures affect quantitatively the cyclical behavior in the two areas: the magnitude of the credit channel effects is amplified by the differences in the financial structures. We further demonstrate that the effects of minor differences in the credit market translate into large, persistent and asymmetric fluctuations in price of capital, bankruptcy rate and risk premium. The effects imply that the Euro Area's supply elasticities for capital are less elastic than the U.S.
Keywords: E4; E5; E2; 330; agency costs; credit channel; investment behavior; E.U. area; Anlageverhalten; Prinzipal-Agent-Theorie; Schätzung; EU-Staaten; USA